DISEÑO DE UNA GUÍA METODOLÓGICA PARA FOMENTAR LA PRÁCTICA DE ECUAVOLEY EN JÓVENES DE 14-16 AÑOS DEL BARRIO DELIA CRISTINA DE LA PARROQUIA LA UNIÓN AÑO 2023. - PINCAY AGUILAR DANNY JOSUE (2024)
The practice and promotion of Ecuavoley has been promoted in recent times by different factors that are part of the economic, cultural and social context, generating increasingly greater expectations that are causing this activity to reach an important connotation, generating expectations for this variant of volleyball. . in all areas of society. In that sense, the present study has the objective of promoting the practice of this sport for which it is planned to design a methodological guide to promote the practice of Ecuavoley in young people aged 14-16 from the Delia Cristina neighborhood, from the La Unión Parish. A mixed, descriptive, non-experimental cross-sectional research design was used. The interview and survey were applied as diagnostic methods. a non-probabilistic sample selected and made up of 24 young people aged 14-16 years present in the population, among them 17 men (70.83%) with an average age of 15.6 years and 7 women (29.17%) with an average age of 14.8 years. Among the expected results, it is intended to direct the design of a methodological guide to promote the practice of Ecuavoley in the young inhabitants of 14-16 years of age of the Delia Cristina neighborhood, of the La Unión Parish, year 2023.